Nikah Siri dan Isbat Nikah dalam Perspektif Fiqh Ahwal Syakhsiyah: Antara Keabsahan Syariat, Kepastian Hukum, dan Perlindungan Perempuan serta Anak - Fauziah Hanum; Heri Firmansyah (Tabayyun : Journal Of Islamic Studies, 2026)
Unregistered marriage (nikah siri) remains a persistent issue in Indonesian Islamic family law due to the tension between religious validity and state legal certainty. Previous studies have generally examined unregistered marriage from separate perspectives, including Islamic legal validity, social consequences, or marriage validation procedures (isbat nikah). However, comprehensive studies integrating fiqh ahwal syakhsiyah, Indonesian positive law, and the protection of vulnerable groups remain limited. This article aims to analyze the legal position of unregistered marriage and marriage validation within the framework of fiqh ahwal syakhsiyah by emphasizing the relationship between religious legitimacy, legal certainty, and the protection of women and children. This study employs normative legal research using statutory, conceptual, and maqashid al-sharia approaches. Primary legal materials consist of Indonesian marriage laws, the Compilation of Islamic Law, regulations on marriage registration, and Constitutional Court decisions concerning children's legal status. The findings reveal that unregistered marriage may be considered valid under Islamic jurisprudence when its pillars and conditions are fulfilled; however, it fails to provide adequate legal certainty within the national legal system. Marriage validation through the Religious Court functions as a corrective mechanism bridging religious validity and state legality. From the perspective of maqashid al-sharia, marriage registration serves as an instrument for protecting hifz al-nasl (lineage), hifz al-mal (property), and hifz al-'ird (honor), thereby safeguarding the rights of women and children. The study concludes that the integration of fiqh norms and state administrative mechanisms is consistent with the objectives of Islamic law in promoting family welfare and legal protection.